STREATEGI KOMUNIKASI PEMASARAN TERPADU PT. GO-JEK INDONESIA BRANCH BALi DALAM MEMBENTUK BRAND AWARENESS - Mahayuni, Putu Yurika Ari; Purnawan, Ni Luh Ramaswati; Cahyani, Dewi Yuri (E-Jurnal Medium, 2017)
ABSTRAK   The goal of this research is to describe and to explain the integrated marketing communication strategic od Go-Jek Branch Bali in establishing brand awareness among the expatriate. This research uses descriptive qualitative approach. Informants are chosen by purposive technique and snowball. The data obtained through interview, direct observation, and documentation study. As for the analysis techniques used in this research is through several step, which is data reduction, presentation, and conclusion. The results showed that Go-Jek Branch Bali uses the integrated marketing communication strategy in establishing brand awareness among the expatriate. Although it has a diverse audience segmentation, Go-Jek Branch Bali using the similar integrated marketing communication but adapted in terms of language. In addition, Go-Jek Branch Bali are focusing the marketing communication in digital by utilizing social media. In delivering the message, Go-Jek Branch Bali deliver a similar message to every communication channel but without including keywords so the message would look different.   Keywords: integrated marketing communication, Go-Jek Branch Bali, Expatriate